1999
DOI: 10.1002/(sici)1521-3757(19991216)111:24<3916::aid-ange3916>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselektive Addition von Allyltrimethoxysilanen an Aldehyde mitp-Tol-BINAP⋅AgF als Katalysator

Abstract: Allyltrialkoxysilane sind als reaktive Allylsilane bekannt, da sie bei der Reaktion mit Nucleophilen pentakoordinierte Silicate bilden. [1] Diese Allylsilicate werden bisweilen zur Allylierung von Carbonylverbindungen unter basischen Bedingungen eingesetzt, [2] aber so weit uns bekannt ist, wurde bisher über keine asymmetrische Reaktion dieser Reagentien berichtet. Wir berichten im folgenden über die erste asymmetrische Addition von Allyltrimethoxysilanen an Aldehyde, die durch p-Tol-BINAP´AgF katalysiert wir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Our group reported the first example of asymmetric silver‐catalyzed addition of allyltrimethoxysilanes to aldehydes 5. Recently we have demonstrated that these conditions can be successfully applied to a highly diastereo‐ and enantioselective allylation of ketones 6.…”
Section: Resultsmentioning
confidence: 99%
“…Our group reported the first example of asymmetric silver‐catalyzed addition of allyltrimethoxysilanes to aldehydes 5. Recently we have demonstrated that these conditions can be successfully applied to a highly diastereo‐ and enantioselective allylation of ketones 6.…”
Section: Resultsmentioning
confidence: 99%